Determinants That Affect Going Concern Audit Opinion - Andriyanto, Rio; Srianti, Amani; Ayu, Putri Puspita (International Journal of Business, Economics, and Social Development, 2024)
Companies listed on the Indonesia Stock Exchange (IDX) in the consumer goods industry will be the focus of this study, which aims to analyze the influence of going concern audit views on these companies using financial and non-financial factors. These factors include profitability, leverage, liquidity, firm size, and the previous year's audit opinion. Throughout the study period, secondary data was culled from the following sources: yearly financial statements and independent auditor reports of every firm listed on the IDX in the consumer products industrial category. The sample population consisted of 107 IDX-listed consumer products businesses from 2020 to 2022. Using a purposive sampling technique, 132 observations were collected over the course of three years from 44 qualifying enterprises in the consumer products industry. Utilising SPSS version 25, Logistic Regression Analysis was used as the data analysis approach.This research shows that profitability, leverage and going concern audit opinions in the previous year have a significant positive influence on going concern audit opinion making, then liquidity and company size have a significant negative influence on going concern audit opinion taking.